Shelf life extension of vacuum-packed salt reduced frankfurters and cooked ham through the combined application of high pressure processing and organic acids. (September 2018) - O' Neill, Ciara M.; Cruz-Romero, Malco C.; Duffy, Geraldine; Kerry, Joseph P.
Highlights: High pressure processing (HPP) and a mix of organic acids were used as hurdles. The hurdles applied extended the shelf life of low-salt frankfurters and cooked ham. Hurdle technology can compensate for loss of safety/shelf life due to salt reduction. While physicochemical changes occurred; sensory acceptability did not change. Abstract: The objective of this study was to assess the efficacy of a combination of high pressure processing (HPP) and a mix of organic acids Inbac ™ as hurdles to extend the shelf life of previously optimised sensory accepted frankfurters and cooked ham with significantly ( P  < 0.05) lower salt content. The optimum parameters for the manufacture of low-salt frankfurters were; Salt replacer Artisalt ™ (48%), HPP (580 MPa) and Inbac ™ (0.3%) and for manufacture of low-salt cooked ham the optimum parameters were; Salt replacer Artisalt ™, HPP (535 MPa) and Inbac ™ (0.3%). Physicochemical changes ( P  < 0.05) occurred over storage time; however, the sensory acceptability did not change significantly. From the microbiological point of view, the results indicated that the hurdles (HPP and Inbac™) applied in the manufacture of low-salt processed meat products extended ( P  < 0.05) the shelf-life of low-salt frankfurters by 51% and low-salt cooked ham by 97%, compared to control samples which contained full salt content. These results highlight the potential use of the hurdle strategy for extending the shelf-life and safety of low-salt processed meat products.